An Investigation of Secondary School Students’ Anxiety and Motivation Levels towards Science Course in Terms of Some Variables - CAYMAZ, Belkız; AYDIN, Abdullah (Bilge Akademi, 2022)
This work aims at studying the anxiety and motivation levels of secondary school students towards science course depending on gender, class levels, and their parents’ level of education. In addition, it was aimed to examine the relationship between students' anxiety, motivation, and academic achievement towards science course. The study relies on a relational scannig model within the context of the general scannig model. The research sample consist of 629 students who continue their education at public secondary school in Kastamonu Province, Turkey, in the 2019-2020 academic year. Anxiety Scale for Science Course, Motivation Scale for Science Learning, Personal Information Form, and science grade for the end of the first semester were used as data collection tools in the research. The data obtained from the research were analyzed using the SPSS 22 program. As a result of this study, it is found out that the secondary school students' science anxiety levels were incredibly low but, their motivation levels towards science course were high. Also, it was observed that there was a significant relationship between students’ science anxiety, science motivation and academic achievement. As to gender, it was determined that there was no significant difference between students' anxiety towards science course, and a significant difference between motivation towards science course. In addition, it was determined that students' anxiety and motivation towards science course differ significantly depending on class levels and their parents’ level of education.
Keywords: Alan Eğitimleri; Other Fields of Education; Anxiety; motivation; academic achievement; science course; secondary school students; 4. Education